Treatment outcomes of paul versus ahmed glaucoma implants - Julia Prinz; Kira Hilmers; Constance Liegl; Peter Walter; Karl Mercieca; Verena Prokosch (PLoS ONE, 2025)
Objectives To compare the outcomes of Paul (PGI) and Ahmed glaucoma implants (AGI) in patients with complex glaucoma. Methods 64 patients undergoing PGI and 40 patients undergoing AGI were included in this study. Intraocular pressure (IOP), the number of IOP-lowering eye drops, and complications were evaluated during an 18-month follow-up. Results At 18 months, follow-up was completed by 26 patients (65.0%) in the AGI group and 45 patients (70.3%) in the PGI group. IOP was significantly reduced 18 months following PGI (12.3 ± 4.0 vs. 28.0 ± 9.3 mmHg, p < 0.001) and AGI (15.6 ± 5.2 vs. 30.7 ± 8.9 mmHg, p < 0.001) compared to preoperatively. The PGI achieved significantly lower IOP compared to the AGI group (p = 0.042). Similarly, the use of IOP-lowering eye drops decreased significantly at 18 months in the PGI (0.5 ± 0.8, p < 0.001) and AGI (1.3 ± 1.0, p < 0.001) groups, from baseline values of 3.3 ± 1.3 in PGI and 3.5 ± 1.3 in AGI. The number of IOP-lowering eye drops was significantly lower in the PGI than in the AGI group at both 12 (p = 0.031) and 18 months (p = 0.018). At the 18-month follow-up, qualified success rates for target pressures ≤18 mmHg were higher after PGI than AGI (IOP ≤ 18 mmHg: 66.6% vs. 84.2%, p = 0.017, ≤ 15 mmHg: 46.3% vs. 64.8%, p = 0.049, ≤ 12 mmHg: 24.9% vs. 43.0%, p = 0.047). There was no significant difference in the complication rates between PGI and AGI. Conclusion Both PGI and AGI effectively reduced IOP and the number of IOP-lowering eye drops over an 18-month follow-up period. The PGI demonstrated significantly greater reductions in IOP and IOP-lowering eye drops than AGI at 18 months. The safety profiles of PGI and AGI were comparable.